Formulação estratégica no CIEE Lisboa - Lopes da Costa, R. (2019)
In an era in which the market is increasingly competitive and globalized, companies are forced to rethink and innovate their strategy. This investigation aims to determine if CIEE Lisbon is implementing corporate strategies in order to reach its strategic goals and increase its business performance. This study used a qualitative methodology based on detailed content analysis of 18 interviews. The article concludes that CIEE is implementing diversification strategies that allow it to grow organically and to create barriers to new competitors. It is also possible to conclude that the formation of strategic alliances is vital in the company's success, having a direct and positive impact on consumer satisfaction. Finally, this research shows that a merger and/or acquisition is not a viable option for the company at this time.